Evaluasi Ahli pada Model Latihan Strategi Serangan Futsal di Akademi Futsal Surakarta - Subekti, Anjas Asmara; Prasetya, Rezza Adiluhung; Widianto, Brian Kurniawan; Prasetyo, Koko; Sutrisno, Tri (Universitas Mercu Buana Yogyakarta, 2025)
The purpose of this study is to evaluate experts on the futsal attack strategy training model at the Surakarta Futsal Academy. This activity was carried out at the Budi Langgeng Futsal Field, Jetis Village, Sawahan Village, Ngemplak District, Boyolali Regency. This research was carried out at the Budi Langgeng Futsal Field, Jetis Village, Sawahan Village, Ngemplak District, Boyolali Regency. This type of research uses a quantitative descriptive method. The data analysis technique for the expert and futsal player questionnaires is a descriptive percentage analysis technique. The implementation of this expert evaluation is to obtain responses and input from experts for the perfection of the product, in this case the futsal strategy training model. In implementing this expert, an instrument is used as an evaluation tool for the development product. The percentage result of the expert evaluation is 83.48%. The conclusion of this study is that the results of the evaluation of the appointed expert practitioners and academic experts are in the form of a percentage of 83.48%, these results can be interpreted that the product development results can be continued to the next stage by considering the suggestions and notes from the experts